10.1016/s1541-9800(12)70130-8 (CrossRef Listing of Deleted DOIs, 2000)
Research before and during COVID-19 has framed health-system resilience as the capacity to absorb shocks, adapt, transform and learn while sustaining essential functions. Building on this broader literature, including Meredith et al.'s account of local public-health adaptation under political and resource constraints, we propose a worker-patient safety loop from a Taiwan psychiatric hospital perspective: workforce strain can weaken safety-critical care; near misses, adverse events and continuity failures should trigger reporting, organisational learning and corrective action; and the resulting changes should protect workers, patients and care continuity. The loop can be monitored through indicators of workforce wellbeing and safety, safety-event learning, and continuity across settings, supported by digital incident, staffing and handoff systems with safeguards for privacy and data quality. Informed by professional experience and published evidence, this conceptual framework applies to acute shocks and continuing operational pressures. Its proposed domains require prospective empirical validation before they can be treated as established measures of hospital resilience.